(untitled) (Boletin Médico de Postgrado, 2020)
Transmitral flow, although its single modification no longer represents a criteria to define diastolic dysfunction, remains the first step for diagnosis. The pseudonormal pattern remains a challenge in terms of its differentiation with the normal or abnormal pattern in the population, however it is interesting to know the prevalence of this pattern in young populations with structurally healthy heart. We performed a descriptive transversal study in 38 patients with a structurally healthy heart and no known cardiovascular disease, who attended the Regional Cardiovascular Center ASCARDIO in the period January-March 2019. A transthoracic echocardiogram was performed where baseline determinations of transmitral flow and subsequent to the application of the Handgrip maneuver were made. The results show that 68% of patients had a pseudonormal pattern of transmitral flow. After performing the Handgrip maneuver, 84% of the individuals showed a normal flow pattern while 6% had a pseudonormal pattern, with an equal distribution by sex. Handgrip maneuver is useful to unmask the pseudonormal to normal pattern of transmitral flow and in the opposite direction, in patients with structurally healthy heart.